Investigation of gas purging configuration in an industrial ladle by computational fluid dynamics - Akbari, Mona; Safaei, Babak; Zarei, Taleb (Aip Publishing, 2023)
A three-dimensional model was developed to investigate the effects of gas nozzle configuration in an industrial gas-stirred ladle on flow pattern, mixing time, heat transfer, inclusion removal, and shear stress on the wall. Population balance model coupled with computational fluid dynamics was chosen to evaluate the inclusion removal. The properties of phases and the size distribution of inclusion were in agreement with literature data. Gas nozzle locations were investigated in terms of radius and angle. It was found that an increase in angle and decrease in radius of gas nozzle location decreased shear stress on the wall. Also, as gas nozzle locations got closer to each other, bubble plumes overlapped, and turbulent kinetics was affected. This in turn affected temperature, mixing time, and inclusion removal. Therefore, by changing angle and radius, these parameters did not have similar trends. From the performed investigations, it was found that the best gas injection location was angle of 140 degrees and radius of 0.65R. Shear stress, mixing time and inclusion removal at ladle with the plug radius of 0.65R were improved by 38.7%, 1.3%, and 0.87%, respectively. In addition, at ladle with the plug angle of 140 degrees, shear stress, mixing time, and inclusion removal were increased by 6%, -6.57%, and 8%, respectively. By choosing this gas injection location, ladle performance was optimum in all parameters.
Keywords: Inclusion Removal; Mixing Phenomena; Stirred Ladles; Mass-Transfer; Steel; Flow; Prediction; Simulation; Convection; Growth